OVAPRIM DOSES EFFECTS ON EGGS OF AFRICAN MUDFISH CLARIAS GARIEPINUS: Life Science-Zoology - NZEH, C.G. ACHIONYE; OBAROH, ISRAEL (International Journal of Life Science and Pharma Research, 2012)
Induced spawning of African mudfish Clarias gariepinus was conducted at different ovaprim doses, to observe the situation that will provide the highest number of eggs. Females of C. gariepinus were injected with different doses of ovaprim 0,5ml/kg, 1.0ml/kg and 1.5ml/kg. The fish in control experiment were injected with 0.0ml/kg of ovaprim. The eggs collected from injected fishes were fertilized with milt from male C. gariepinus. The fertilized eggs from fishes injected with 0.5ml/kg, 1.0ml/kg and 1.5ml/kg were placed in netting fabrics in bowls of water and were placed inside the laboratory. The results obtained showed that increase in the dosage of sGnRHa enhanced the production of more eggs and the highest number of eggs was obtained with 1.5ml/kg of ovaprim. It also reduced ovulation period. The fish that were injected with 0.5ml/kg produced the least amount of eggs and were stressed during the process of removal of eggs resulting in death. A dosage of 1.0ml/kg was recommended for artificial spawning of C. gariepinus for subsistence fish culture because the eggs oozed out directly with slight stroking of the belly of the fish and no mortality was recorded. 1.5ml/kg could be injected if the farmer has the facility to hold large numbers of larvae